2019
DOI: 10.1111/ele.13386
|View full text |Cite
|
Sign up to set email alerts
|

Herbivore consumers face different challenges along opposite sides of the stoichiometric knife‐edge

Abstract: Anthropogenic activities have reshaped the relative supply rates of essential elements to organisms. Recent studies suggested that consumer performance is strongly reduced by food that is either very high or very low in relative phosphorus content. However, the generality of such ‘stoichiometric knife‐edge’ and its underlying mechanisms are poorly understood. We studied the response of a planktonic rotifer to a 10‐fold food carbon : phosphorus (C : P) gradient and confirmed the existence of the stoichiometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 83 publications
1
35
0
Order By: Relevance
“…Many studies have demonstrated that a mismatch between the elemental requirements of consumers and their prey (i.e. 'stoichiometric mismatch') results in altered phenotypes and reduced performance of consumers (Elser et al 2001, Frost and Elser 2002, Zhou and Declerck 2019. However, the role of maternal effects in determining the phenotypic response to stoichiometric mismatch is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that a mismatch between the elemental requirements of consumers and their prey (i.e. 'stoichiometric mismatch') results in altered phenotypes and reduced performance of consumers (Elser et al 2001, Frost and Elser 2002, Zhou and Declerck 2019. However, the role of maternal effects in determining the phenotypic response to stoichiometric mismatch is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Another type of studies uses the method to evaluate the effects of various degrees of P limitation on consumer performance while controlling for indirect, non-stoichiometric effects. Whereas numerous studies in the framework of ES have addressed the effects of P-limitation, few have addressed the response of consumers along very broad ranges of stoichiometric food quality, including treatments with excess P (i.e., food with very low C:P ratios, Plath and Boersma 2001;Zhou and Declerck 2019). Intriguingly, several of these studies have reported unimodal responses to broad food C:P gradients with reduced consumer performance not only at high but also at very low food C:P levels (coined as the 'stoichiometric knife-edge'; Plath and Boersma 2001;Elser et al 2006Elser et al , 2016Bullejos et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…C‐limited) growth to a nutrient‐limited growth. Deviations of food stoichiometry bellow or above the TER induce a dietary (C‐ or nutrient‐) limitation for consumers (Frost et al, 2006) and lead to a unimodal response of growth to food stoichiometry also known as the “stoichiometric knife‐edge” (Elser et al, 2016; Zhou & Declerck, 2019). Besides the effects on consumer performance, the TER can explain consumer‐driven P and N recycling in ecosystems (Cherif & Loreau, 2013), population dynamics (Elser et al, 2000; Frost et al, 2006) and species interactions (Boersma et al, 2016).…”
Section: Introductionmentioning
confidence: 99%